Prison writing and the literary world - Kelly, M (Routledge, 2020)
Prison Writing and the Literary World tackles international prison writing and writing about imprisonment in relation to questions of literary representation and formal aesthetics, the “value” or “values” of literature, textual censorship and circulation, institutional networks and literary-critical methodologies. It offers scholarly essays exploring prison writing in relation to wartime internment, political imprisonment, resistance and independence creation, regimes of terror, and personal narratives of development and awakening that grapple with race, class and gender. Cutting across geospatial divides while drawing on nation- and region-specific expertise, it asks readers to connect the questions, examples and challenges arising from prison writing and writing about imprisonment within the UK and the USA, but also across continental Europe, Stalinist Russia, the Americas, Africa and the Middle East. It also includes critical reflection pieces from authors, editors, educators and theatre practitioners with experience of the fraught, testing and potentially inspiring links between prison and the literary world.